Pemahaman Tentang Pembagian Warisan Yang Adil Dalam Perkara Perebutan Hak Waris Sesuai Prosedur Di Tinjau Dari Pasal 195 Ayat (1) Kompilasi Hukum Islam di Desa Posso - Adistia R. Nur; Nur Mohamad Kasim; Dolot Alhasni Bakung (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The aim of this activity is to provide an understanding of the fair distribution of inheritance in cases of fighting over inheritance rights using several types of settlement methods. To give people an understanding that the position of a will is very important in Indonesia and even if it is not carried out according to existing procedures then the will is not legally valid. This type of research is normative-empirical legal research. According to Abdulkadir Muhammad, what is meant by normative-empirical legal research (applied law research) is research that uses normative-empirical legal case studies in the form of legal behavioral products. The results of the research obtained regarding the granting of wills that did not comply with procedures were that there were conflicting norms due to the public's lack of understanding of the regulations for granting valid wills. In conclusion, the legal status of wills will be very well maintained if the community is able to apply the legal procedures that the law has established because everything we do will definitely be directly related to the law, as we know as citizens of Indonesia, we are a country that upholds the law. justice for human rights, in its application laws are made to provide legal certainty to the community, it only remains for the community itself to be able to implement it or not, because if seen from a civil law perspective, everything that is done by humans is not in accordance with the law. existing then the action can be null and void by law.